IFIT2‐depleted metastatic oral squamous cell carcinoma cells induce muscle atrophy and cancer cachexia in mice. Issue 2 (15th February 2022) - Lai, Kuo‐Chu; Hong, Zi‐Xuan; Hsieh, Jyh‐Gang; Lee, Hui‐Ju; Yang, Muh‐Hwa; Hsieh, Chia‐Husu; Yang, Cheng‐Han; Chen, Yan‐Ru
Abstract: Background: Interferon‐induced protein with tetratricopeptide repeat 2 (IFIT2) is a reported metastasis suppressor in oral squamous cell carcinoma (OSCC). Metastases and cachexia may coexist. The effect of cancer metastasis on cancer cachexia is largely unknown. We aimed to address this gap in knowledge by characterizing the cachectic phenotype of an IFIT2‐depleted metastatic OSCC mouse model. Methods: Genetically engineered and xenograft tumour models were used to explore the effect of IFIT2‐depleted metastatic OSCC on cancer cachexia. Muscle and organ weight changes, tumour burden, inflammatory cytokine profiles, body composition, food intake, serum albumin and C‐reactive protein (CRP) levels, and survival were assessed. The activation of the IL6/p38 pathway in atrophied muscle was measured. Results: IFIT2‐depleted metastatic tumours caused marked body weight loss (−18.2% vs. initial body weight, P < 0.001) and a poor survival rate ( P < 0.01). Skeletal muscles were markedly smaller in IFIT2‐depleted metastatic tumour‐bearing mice (quadriceps: −28.7%, gastrocnemius: −29.4%, and tibialis: −24.3%, all P < 0.001). Tumour‐derived circulating granulocyte‐macrophage colony‐stimulating factor (+772.2‐fold, P < 0.05), GROα (+1283.7‐fold, P < 0.05), IL6 (+245.8‐fold, P < 0.001), IL8 (+616.9‐fold, P < 0.001), IL18 (+24‐fold, P < 0.05), IP10 (+18.8‐fold, P < 0.001), CCL2 (+439.2‐fold, P < 0.001), CCL22 (+9.1‐fold, P < 0.01) and tumour necrosis factor α (+196.8‐fold, P < 0.05) were elevated in IFIT2‐depleted metastatic tumour‐bearing mice. Murine granulocyte colony‐stimulating factor (+61.4‐fold, P < 0.001) and IL6 (+110.9‐fold, P < 0.01) levels were significantly increased in IFIT2‐depleted metastatic tumour‐bearing mice. Serum CRP level (+82.1%, P < 0.05) was significantly increased in cachectic shIFIT2 mice. Serum albumin level (−26.7%, P < 0.01) was significantly decreased in cachectic shIFIT2 mice. An assessment of body composition revealed decreased fat (−81%, P < 0.001) and lean tissue (−21.7%, P < 0.01), which was consistent with the reduced food intake (−19.3%, P < 0.05). Muscle loss was accompanied by a smaller muscle cross‐sectional area (−23.3%, P < 0.05). Muscle atrophy of cachectic IFIT2‐depleted metastatic tumour‐bearing mice (i.v.‐shIFIT2 group) was associated with elevated IL6 (+2.7‐fold, P < 0.05), phospho‐p38 (+2.8‐fold, P < 0.05), and atrogin‐1 levels (+2.3‐fold, P < 0.05) in the skeletal muscle. Neutralization of IL6 rescued shIFIT2 conditioned medium‐induced myotube atrophy (+24.6%, P < 0.01). Conclusions: Our results suggest that the development of shIFIT2 metastatic OSCC lesions promotes IL6 production and is accompanied by the loss of fat and lean tissue, anorexia, and muscle atrophy. This model is appropriate for the study of OSCC cachexia, especially in linking metastasis with cachexia.